Role of hysterolaparoscopy in the diagnosis and management of infertility - Agrawal, Saumya P.; Kedia, Noopur; Jani, Shashwat K.; Agrawal, Siddharth P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Infertility is defined by WHO and ICMART as a disease of the reproductive system by the failure to achieve a clinical pregnancy after 12 months or more regular unprotected sexual intercourse. Objective of this study were to assess the role of hysteroscopy and laparoscopy in the evaluation of female infertility. To assess the therapeutic role of these endoscopic modalities in cases of infertility. Methods: A prospective study of 112 women coming with the complain of infertility to a tertiary care centre hospital in Ahmedabad over a period of 30 months from January 2017 to June 2019. Results: Of the 112 cases, 69.7% had primary infertility and 30.3% had secondary infertility. Septum was the most common hysteroscopic finding (7.1%) followed by polyps (5.4%) and synechiae (3.6%). Adhesions was the most common laparoscopic finding (23.2%) followed by tubal blocks (19.7%) and fibroid (17.9%). Polycystic ovaries were seen in 12.5% patients followed by endometriosis in 10.7% women. Myomectomy was most common therapeutic procedure (17.9%) followed by adhesiolysis in 14.3% women and PCO drilling in 8.9% women. Conclusions: Hysterolaparoscopy is useful as a diagnostic and therapeutic measure for women having infertility.